2017
DOI: 10.1289/ehp73
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Benefits of Wearing Particulate-Filtering Respirators: A Randomized Crossover Trial

Abstract: Background:Practical approaches to protect individuals from ambient particulate matter (PM) are urgently needed in developing countries. Evidence on the health benefits of wearing particulate-filtering respirators is limited.Objectives:We evaluated the short-term cardiovascular health effects of wearing respirators in China.Methods:A randomized crossover trial was performed in 24 healthy young adults in Shanghai, China in 2014. The subjects were randomized into two groups and wore particulate-filtering respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 26 publications
2
52
0
9
Order By: Relevance
“…We observed altered HRV parameters and HR after short‐term reductions in exposure to PM, consistent with 2 previous respirator intervention studies . In addition, we found significant elevations in HF power, rMSSD and pNN50, and decreases in LF/HF and HR, all of which highlight a predominance of parasympathetic tone.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We observed altered HRV parameters and HR after short‐term reductions in exposure to PM, consistent with 2 previous respirator intervention studies . In addition, we found significant elevations in HF power, rMSSD and pNN50, and decreases in LF/HF and HR, all of which highlight a predominance of parasympathetic tone.…”
Section: Discussionsupporting
confidence: 90%
“…We observed altered HRV parameters and HR after short-term reductions in exposure to PM, consistent with 2 previous respirator intervention studies. 19,20 In addition, we found significant elevations in HF power, rMSSD and pNN50, and decreases in LF/HF and HR, all of which highlight a predominance of parasympathetic tone. In accordance with our study, a previous panel study found that reduced air pollution levels due to intensive air pollution control measures during the Olympic Games (including vehicle restriction and closure of air polluting factories) improved HRV indices in healthy taxi drivers in Beijing.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The better masks can have benefits, even for healthy individuals 9 . In a recent study evaluating the short-term cardiovascular health effects of wearing particulate respirators, researchers from Fudan University in Shanghai and Texas A&M University’s School of Public Health measured heart rate variability and blood pressure in 24 healthy young adults with and without masks.…”
Section: Air Pollution Exposuresmentioning
confidence: 99%
“…5,13 Indeed, findings by this same group of investigators recently demonstrated favorable changes in blood pressure and other biomarkers when healthy young adults in Shanghai wore N95 respirators. 14 Given the danger posed by air pollution and the short-term benefits of personal-protection strategies (indoor air filtration and N95 facemasks) on improving surrogate health end points, why have these relatively inexpensive practical approaches not been promoted to the public at-large by scientific and health agencies? 3,4 The answer is that there have been no large-scale randomized controlled outcome studies with hard cardiovascular end points (eg, acute coronary syndromes, strokes, heart failure) to conclusively support the basis for any such formal recommendations in any population.…”
mentioning
confidence: 99%